2019
DOI: 10.1161/strokeaha.118.023682
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association Between HDL (High-Density Lipoprotein) Cholesterol and Stroke Risk Among Patients With Type 2 Diabetes Mellitus

Abstract: Background and Purpose-Very few studies have assessed the association of high-density lipoprotein (HDL) cholesterol with stroke risk among patients with type 2 diabetes. We aimed to investigate the association of HDL cholesterol with total and type-specific stroke risk in patients with type 2 diabetes. Methods-We performed a retrospective cohort study of 27,113 African Americans and 40,431 whites with type 2 diabetes. Cox proportional hazards regression models were used to estimate the association of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
6
17
0
Order By: Relevance
“…A study including multivariate analysis conducted in Spain found 41.2% T2DM patients with atherothrombotic stroke and 35.1% with lacunar infarction ( 18 ). Shen et al ( 19 ) performed a retrospective cohort study composed of 27,113 blacks and 40,431 whites with T2DM and found that 8,496 (12.57%) participants developed stroke during a mean follow-up period of 3 years. A Chinese study was conducted on 9,374 T2DM patients in total to establish a risk score system; among all the participants, 11.48% developed ischemic stroke with a mean follow-up of 8 years ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study including multivariate analysis conducted in Spain found 41.2% T2DM patients with atherothrombotic stroke and 35.1% with lacunar infarction ( 18 ). Shen et al ( 19 ) performed a retrospective cohort study composed of 27,113 blacks and 40,431 whites with T2DM and found that 8,496 (12.57%) participants developed stroke during a mean follow-up period of 3 years. A Chinese study was conducted on 9,374 T2DM patients in total to establish a risk score system; among all the participants, 11.48% developed ischemic stroke with a mean follow-up of 8 years ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis on data of 61 studies indicated a strong association between HDL-C cholesterol and high risk of CVD and death ( 48 ). Through a retrospective cohort study and a mean follow-up of 3 years, including 67,544 T2DM patients, a significant adverse connection was found between HDL-C cholesterol among T2DM patients and the risk of total, ischemic, and hemorrhagic stroke ( 19 ). High-density lipoprotein cholesterol was an influencing factor involved in a Chinese retrospective cohort study aiming at establishing a predictive model of ischemic stroke among T2DM patients ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from patients with type 2 diabetes in the Louisiana Experiment Assessing Diabetes outcomes (LEAD) cohort study were obtained through the Research Action for Health Network (REACHnet) 9,10 . The dataset included electronic health record data for the study cohort from 1 January 2013 to 30 April 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Data on patients with type 2 diabetes in the Louisiana Experiment Assessing Diabetes outcomes (LEAD) cohort study were obtained through the Research Action for Health Network (REACHnet). 6,7 REACHnet is a partnership of health systems, academic centers, and public health organizations that constitute an innovative data network for conducting efficient, multi-site research. Data from three REACHnet partner health systems were used in the current study including Ochsner Health System, Tulane Medical Center, and Access Health Louisiana.…”
Section: Study Participantsmentioning
confidence: 99%